Dual Band Terahertz Reflective Linear Cross Polarization Converter-Based Biosensor - Maurya, Vikram; Singhal, Sarthak (IEEE sensors journal, 2024)
In this article, a dual-band electromagnetic reflective linear cross polarization converter (RLCPC) for terahertz applications is proposed. The proposed polarization converter consists of a hexagonal split ring-shaped metallic resonator, dielectric material, and conductive ground plane. The overall dimensions of the proposed polarization converter unit cell are 20× 20× 4.2\,\,μ \text{m} . It has polarization converter ratio (PCR) ≥90 % over a band of 0.0773 and 0.3754 THz centered at 2.912 and 5.905 THz, respectively. The full-width at half-maximum (FWHM) of the two bands are 0.349 and 1.1934 THz. This converts {x} -pol. wave to {y} -pol. and vice versa. It has incident angle ( θ ^{° } ) stability for θ ≤35^{° } . A good agreement between the computer simulation technology (CST MWS), high-frequency structure simulator (HFSS), and equivalent circuit model (ECM) results was observed. The suitability of the proposed converter for refractive index (RI) sensing, biosensing, and glucose detection application is also analyzed and presented. A minimum and maximum sensitivity of 300 and 700 GHz/RIU respectively are achieved for the proposed RLCPC-based sensor. In the case of cancer, tumor, and glucose detection, the proposed sensor achieves maximum sensitivity of 0.6346, 0.773, and 0.6886 THz/RIU, respectively. The RI of unknown samples is approximated with a %error between 0% and 0.8% subject to the availability of precise sample data. This converter has merits of compact dimensions, single layer geometry, incident angle ( θ ^{° } ) stability up to 35°, wider FWHM, and high sensitivity over other converters.